MONOPOLE ANTENNA PERFORMANCE AT VARIED FEED POSITIONS - Ikechiamaka, F. N.; Okpala, C. N.; Abdullahi, B. H. (FUDMA JOURNAL OF SCIENCES, 2023)
Two simple monopole antennas mounted on finite ground planes are presented. The antennas designed to operate at 900 MHz and 1800 MHz respectively are simulated using High Frequency Structural Simulator (HFSS). The study reveals that variation in feed position from the edge of width of ground plane leads to slight increase in resonance frequency and return loss but decrease in antenna gain. An enhancement in gain can be achieved (up to 5% and 40 % for antennas tuned at 900 MHz and 1800 MHz respectively) when the feed is placed at the edge of the ground plane. On the other hand, an increase in bandwidth of 33.3% and 4% was observed when the feed is positioned at the center of the width of ground plane for 900MHz and 1800MHz tuned antennas respectively. Therefore for optimal monopole antenna performance, the choice of feed position should be made based on the application of interest.